Entropy parameters for falling film absorber optimization. (25th January 2016) - Giannetti, Niccolò; Rocchetti, Andrea; Lubis, Arnas; Saito, Kiyoshi; Yamaguchi, Seiichi
Highlights: Local entropy generation analysis of an absorptive film on a cooled horizontal tube. Parametric study of the entropy generation related to various irreversibility sources. Identification of the least irreversible solution mass flow-rate. Parameters accounting for the irreversibility are used as optimization criterion. Graphical Abstract: Abstract: A local entropy generation analysis, for water vapor absorption in LiBr-H2 O solution, is performed referring to velocity, temperature and concentration fields obtained from the numerical solution of mass and energy transport equations. The hydrodynamic description is based on Nusselt boundary layer assumption and the actual amount of irreversibility introduced is determined for an absorptive falling film over a cooled horizontal tube inside the absorber. Results are explored in different operative conditions in order to examine the impact of the various irreversibility sources in a wide operative range. A least irreversible solution mass flow-rate can always be identified. Furthermore, a simple and general thermodynamic analysis, carried out regarding a refrigerating and a heat boosting applications, makes evidence of a dimensionless group "Q/σT" that separates the weight of the irreversibilities and gives the way to an optimization criterion applied to the absorber in order to improve the whole system efficiency. Both thermodynamic equilibrium and sub-cooling conditions of the solution at the inlet are considered for typical temperature and concentration of refrigerators' absorbers and heat transformers' absorbers. Results suggest the importance to work at reduced mass flow-rates with a thin uniform film. In practice, tension-active additives are required to realize this condition. Also, it is highlighted that the two parameters defined with reference to the dimensionless group "Q/σT" can be maximized by specific values of the tube radius, operative Reynolds number, solution sub-cooling and temperature difference between the wall and the inlet solution.